SIFAT FUNGSIONAL PATI GARUT HASIL MODIFIKASI HIDROKSIPROPILASI DAN TAUT SILANG [Functional Properties of Hydroxypropylated and Crosslinked Arrowroot Starch] - Rijanti Rahaju Maulani; Dedi Fardiaz; Feri Kusnandar; Titi Candra Sunarti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
Dual-modified arrowroot starch using hydroxypropylation and cross-linking methods was carried out to overcome the deficiency in of native arrowroot starches for food processing application. The modification applied the combination concentration of propylene oxide (8, 10, and 12%) and ratio of sodium trimetaphosphate (STMP):sodium tripolyphosphate (STPP) (1%:4%, 2%:5%, and 3%:6%). The resulting dual-modified arrowroot starches had lower gelatinization temperature (68.45–70.00ºC) than that of native arrowroot starch (72.85ºC). The modified arrowroot starches also had a higher peak viscosity (>5500 cp) than that of native arrowroot starch (4209 cP). Breakdown and setback viscosity of modified arrowroot starch was higher values than the native. At acidic pH, the viscosity decreased at different levels of temperature changes as compared to that of normal pH. Modified starch made with 8% propylene oxide and ratio of STMP: STPP 2%:5% and 3%:6%; as well as that made with 10% propylene oxide and 1% STMP:4% STPP had the lowest syneresis tendency. Decrease in the paste clarity occured with increasing concentration of STMP:STPP. The sedimentation volume of the modified starch was higher (29.17-35.83%) than that of native starch (28.08%), except for those made with 1% STMP: 4% STPP at concentration of propylene oxide 8% and 12%. The gel strength increased (61.77-78.97 gf) at 8% propylene oxide, but decreased (66.50-47.77 gf) at higher concentrations.